2021
DOI: 10.28991/scimedj-2021-0301-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-site Evaluation (ROSE) for Fine Needle Aspiration of Thyroid: Is It Helpful?

Abstract: Introduction: Thyroid nodules are very common. Many are detected incidentally due to increased head and neck imaging. The majority are benign; however, malignancy can’t be excluded in many cases and tissue sampling is needed. Ultrasound guided fine needle aspiration is an easy and effective way to sample g thyroid nodules. Inadequate sampling was reported in 10-40% of the cases. Rapid On-site Evaluation (ROSE) was proposed to assess obtained sample for adequacy. The aim of this study is to identify the benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…Lastly, we merged the subcategory artifacts of Bethesda I, III, and V to assess overall artifacts within ROSE and non-ROSE, respectively. ROSE is not expected to significantly affect the Bethesda IV rate (10,11). However, the rate of Bethesda IV may vary between different centers.…”
Section: Categorization Of Cytology Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, we merged the subcategory artifacts of Bethesda I, III, and V to assess overall artifacts within ROSE and non-ROSE, respectively. ROSE is not expected to significantly affect the Bethesda IV rate (10,11). However, the rate of Bethesda IV may vary between different centers.…”
Section: Categorization Of Cytology Resultsmentioning
confidence: 99%
“…For example, in one study, the introduction of ROSE decreased the non-diagnostic rate by more than 30% (2). By contrast, few studies reported no significant influence of ROSE on specimen adequacy (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound guided fine needle aspiration (US-FNA) is the most commonly available way to evaluate thyroid nodules. However, rapid On-Site Evaluation (ROSE) is found to be the most helpful with small sized nodules or nodules that are more difficult to sample for less experienced radiologists [ 2 ]. Patients with PTC have a > 90% 10-year survival rate after proper surgical treatment and radiotherapy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer (THCA) is the most common form of endocrine cancer worldwide and the number of THCA cases is icreasing [ 1 ]. Thyroid nodules are one of the most common clinical findings [ 2 ]. THCA can be divided into at least four subtypes, papillary thyroid carcinoma (PTC), follicular thyroid cancer (FTC), medullary thyroid cancer (MTC) and anaplastic thyroid cancer (ATC), based on the histological features of a THCA tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Many diseases need to be examined and detected as early as possible (8)(9)(10). The delayed diagnosis of hearing impairment may have serious harmful effects on the development of newborn's language, social, emotional, cognitive, academic, and vocational abilities (11).…”
Section: Discussionmentioning
confidence: 99%